Pembuatan Bioplastik dengan Penguat ZnO dan Penambahan Minyak Atsiri sebagai Anti Mikroba - Fitri Takribiah; Harunsyah Harunsyah; Zuhra Amalia; Reza Fauzan; Muhammad Sami (Jurnal Teknologi, 2022)
Environmental problems caused by petroleum-derived plastic waste has become an important issue because it is difficult to degrade the environment. Therefore, attempts have been made to speed up the process of degradation of the polymer material is to replace synthetic polymers with natural poimer. Starch is a natural polymer that can be used for the production of material that is easily degraded, the raw material is abundant, but has a weakness in its mechanical properties. To improve the mechanical strength of starch, a reinforcing material in the form of inorganic material is usually added in a polymer matrix. In addition to improving shelf life in a plastic made from natural polymers required additional antimicrobial. Therefore, bioplastics prepared by mixing cassava starch as a matrix, glycerol as a plasticizer, ZnO as an amplifier, and clove oil as an antimicrobial. The optimum conditions to produce bioplastics with the highest tensile strength of 23.40 kgf /mm2 given by the addition of 0.8% of ZnO and 0.4 ml clove oil. While the highest percent elongation on the addition of ZnO 1% and 0.4 ml clove oil which is 346.00%. Based on the test results of water resistance and biodegradability, clove oil shown to inhibit the growth of microorganisms bioplastics and bioplastic IR spectra do not show any new functional group.